1986
DOI: 10.1002/bjs.1800730605
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of mucosal carcinoma of the stomach with lymph node metastasis in eleven patients

Abstract: Of 568 patients with mucosal carcinoma of the stomach, only 11 (1.9 per cent) had a lymph node metastasis. The clinicopathological findings in these 11 patients are reviewed. Diameters of the lesions were over 2.0 cm. Seven were located in the body of the stomach and four in the antrum. Nine showed depressed lesions comprised of poorly differentiated adenocarcinoma and two were classed as elevated lesions consisting of well and moderately differentiated adenocarcinomas. There were six with accompanying peptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
3

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 6 publications
6
38
3
Order By: Relevance
“…It is well established that, as the depth of gastric carcinoma invasion into the gastric wall increases, the frequency and the degree of nodal metastasis also increases. Lymph nodal metastasis is present in 1.8-4.8% of EGC patients with mucosal invasion, but in 16.7-23.8% of those with submucosal invasion (Habu et al, 1986;Korenaga et al, 1986;Ohta et al, 1987;Iriyama et al, 1989;Sowa et al, 1989;Inoue et al, 1991;Moreaux and Bougaran, 1993). Thus, the local invasiveness of EGC may be correlated with the survival rate (Lawrence and Shiu, 1991).…”
Section: Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that, as the depth of gastric carcinoma invasion into the gastric wall increases, the frequency and the degree of nodal metastasis also increases. Lymph nodal metastasis is present in 1.8-4.8% of EGC patients with mucosal invasion, but in 16.7-23.8% of those with submucosal invasion (Habu et al, 1986;Korenaga et al, 1986;Ohta et al, 1987;Iriyama et al, 1989;Sowa et al, 1989;Inoue et al, 1991;Moreaux and Bougaran, 1993). Thus, the local invasiveness of EGC may be correlated with the survival rate (Lawrence and Shiu, 1991).…”
Section: Survivalmentioning
confidence: 99%
“…Numerous clinicopathological studies have demonstrated that the frequency of nodal metastasis in EGC with mucosal invasion is less than 5%. The degree of nodal invasion is almost always limited to nl(+), and in less than 1% of the cases with n2( +) (Habu et al, 1986;Korenaga et al, 1986). EGC patients with n2( +) would have been cured only by the ELND procedure but this would have resulted in a comparatively small improvement in the survival rate.…”
Section: Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…In intramucosal cancers, lymph node metastasis was reported to be much less frequent, ranging from 1.9-3.3 %, compared to those in submucosal cancers, about 16.3-20.9 % [11][12][13][14][15]23]. A number of studies reported the incidence of lymphatic involvement in intramucosal cancers and cancers that involved submucosal invasion altogether.…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows enbloc resection of the lesions (1) which has demonstrated to be crucial because the local recurrence rate when this is not possible is of 15 % (2). Nowadays, there is a high experience with ESD in Eastern countries where this technique is considered the gold standard treatment for EGC (3,4).…”
Section: Introductionmentioning
confidence: 99%